PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING UNTUK PESERTA DIDIK KELAS VII SMP - Fazria Rahmawati (Departemen Matematika, 2022)
The purpose of this research is to develop a valid and practical student worksheet based on Discovery Learning on the topic of Statistics. This research used the Plomp model that consists of three phase, which are preliminary research, prototyping stage, and assessment phase. The preliminary research phase consists of needs, student, curiculum, and concept analysis. The prototyping phase is the phase to develop student worksheet based on Discovery Learning on the topic of Statistics. At the development stage through formative evaluation in the form of self evaluation and expert review to get a valid product. The last phase is the assessment phase, with the aim of determining the practicality category of the student worksheet through the one to one and small group evaluation. The results Showed that the student worksheet had a validity level of 85,63% with a very valid category and a practicality level of 95,22% with a very practical category. Keywords – Discovery Learning, Student Worksheet, Statistics.